2021
DOI: 10.1007/s10055-021-00565-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immersive visualization technologies on cognitive load, motivation, usability, and embodiment

Abstract: Virtual reality (VR) is a promising tool to promote motor (re)learning in healthy users and brain-injured patients. However, in current VR-based motor training, movements of the users performed in a three-dimensional space are usually visualized on computer screens, televisions, or projection systems, which lack depth cues (2D screen), and thus, display information using only monocular depth cues. The reduced depth cues and the visuospatial transformation from the movements performed in a three-dimensional spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 133 publications
2
39
3
Order By: Relevance
“…The high usability of our new VR setting, including tactile stimulation, is similar to that in one of the few previous studies in stroke patients with a similar visual and auditory setting, which however did not entail any tactile stimulation [ 14 , 37 ]. Moreover, similar levels of usability have been reported by healthy participants using new VR tools including visual and auditory stimulation, but without tactile stimulation [ 36 , 50 , 51 ]. Hence, in our study, the additional presentation of tactile stimulation did not change usability or cause discomfort.…”
Section: Discussionsupporting
confidence: 61%
“…The high usability of our new VR setting, including tactile stimulation, is similar to that in one of the few previous studies in stroke patients with a similar visual and auditory setting, which however did not entail any tactile stimulation [ 14 , 37 ]. Moreover, similar levels of usability have been reported by healthy participants using new VR tools including visual and auditory stimulation, but without tactile stimulation [ 36 , 50 , 51 ]. Hence, in our study, the additional presentation of tactile stimulation did not change usability or cause discomfort.…”
Section: Discussionsupporting
confidence: 61%
“…Field of view, tactile feedback, and human likeness did not have a significant effect on task performance. The lack of an effect of field of view could be explained by the fact that even if it could affect the SoE, especially the sense of agency as reported in Wenk et al (2021), the reduction of this cue in the suppressive condition did not hamper task execution. This could also be related to both the design of the task, which was simple to accomplish, and the small workspace in which participants had to operate the virtual arm.…”
Section: Discussionmentioning
confidence: 95%
“…Normally, humans have a slightly over 210-degree forward-facing horizontal arc of their visual field, that is, without eye movements (with eye movements included it is slightly larger). It was demonstrated that a reduced field of view affects the sense of agency and can create movement impairments (Wenk et al, 2021).…”
mentioning
confidence: 99%
“…In this immersive virtual environment, the user interacts with a virtual self-representation perceived from first-person perspective (i.e., an avatar), realistically mimicking the body of the user. Previous work has suggested that immersive virtual reality, compared with screens, may further promote motor training because they enhance embodiment over the avatar ( Wenk et al, 2021 ) i.e., the body of the avatar is –at least partially– processed like the own (virtual) body ( Kilteni et al, 2012a ). In the immersive virtual training environment, the user may experience the feeling of body ownership over the avatar.…”
Section: Introductionmentioning
confidence: 99%